Crankcase analysis for two-stroke spark ignition engines - Ting, Swee Keong (2008)
Crankcase of two-stroke spark ignition engine is an important part since it compresses the air fuel mixture before going into cylinder. Parameter inside crankcase such as pressure largely affects the performance of this engine. In this project, the simulation of flow inside of two-stroke engine had been carried out. The objective of this project is to simulate the visualization of crankcase flow process. The advantages of using CFD in this research are low cost and easy to apply compared to the laser. Before the main concept had been applied, COSMOS application is the one of the software that introduces to the basic of flow pattern in this research. After complete the entire tutorial this software, will proceed with the CFD application. CFD application was started by modeling the crankcase in three-dimensional in SOLIDWORK. After that, GAMBIT was use to generate grids before export to FLUENT for flow analysis. Crankcase model was simulated in motoring condition, which means no combustion or firing. As a result, pressure and contours inside the crankcase flow was observed. And found that the simulation results are slightly different from calculation.